A carbon material modified impregnating agent and its preparation method and application

By using carbon material modification impregnant, the composite synergistic effect and secondary curing strengthening of aluminum sol, boron hydroxide and silane impregnant is solved, and the effects of unstable performance and high air permeability of aluminum electrolytic anode materials are achieved, achieving the effect of improving the anode's permeability and service life.

CN119776912APending Publication Date: 2025-04-08HUNAN ZHIQI TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411843184.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing aluminum electrolytic anode materials have problems such as unstable performance, high air permeability, and large carbon consumption, which affect the electrolytic efficiency and aluminum quality.

Method used

A carbon material modified impregnant is used, including aluminum sol, boron hydroxide, silane impregnant and other components. Through the synergistic effect and secondary curing and strengthening, the air permeability and porosity of the anode are reduced, and the conductivity and service life are improved.

Benefits of technology

It significantly reduces the air permeability of the anode, improves the permeability and service life, reduces the gas permeability of carbon materials, and reduces energy consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a carbon material modified impregnating agent and a preparation method and application thereof. The carbon material modified impregnating agent can be used to treat anode materials used in electrolysis processes, and includes: 10 to 70 parts of component A, 5 to 30 parts of component B, 0.5 to 15 parts of component C and a solvent; component A includes at least one of aluminum sol and aluminum silicate sol; component B includes at least one of boron hydroxide, boric acid and borate; component C includes at least one of silane impregnating agent, organic silicon resin and silane coupling agent. The carbon material modified impregnating agent of the present invention can significantly reduce the air permeability of the carbon material, improve the material's anti-permeability and service life, thereby improving the process technical indicators of the carbon material. The main raw material is all organic components, has the advantages of environmental protection, non-toxic and harmless, easy to prepare, etc., and meets the requirements of green production; when applied to the treatment of the anode used in the aluminum electrolysis process, it can significantly reduce the use cost and improve the convenience of use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrolytic anode materials, and in particular to a carbon material modified impregnating agent formula, a preparation method and application thereof. Background Art

[0002] In the aluminum electrolysis process, the anode is the heart of aluminum electrolysis, and its performance has an important impact on the electrolysis efficiency and the quality of aluminum. Traditional anode materials often have problems such as unstable performance and large ineffective consumption. In order to improve the performance of the anode, post-intervention measures can be taken on the anode after it is manufactured. Impregnation, as an effective intervention method, greatly reduces the defects caused by the structural contradiction of internal voids, which can significantly improve the comprehensive performance of the anode, reduce the anode carbon consumption of aluminum electrolysis, and improve the process stability of the electrolytic cell. Therefore, the development of an anode modification impregnating agent with excellent performance has important industrial application value.

[0003] Air permeability is an important indicator of the quality of prebaked anodes. Under the current situation of generally strengthening the current in electrolysis, the air permeability of prebaked anodes has an important impact on the excessive consumption of anodes during electrolysis. The pores inside the anode have a large specific surface area and a high level of gas diffusion coefficient, which results in a strong unbalanced surface reactivity in the internal structure of the prebaked anode, causing the CO 2 The reactivity will be significantly deteriorated, and the thermal shock resistance of the prebaked anode will be weakened, which will lead to an increase in the degree of local air oxidation on the end surface of the prebaked anode during the electrolysis formation.

[0004] In the prior art, the air permeability of the anode is generally reduced by improving the impregnating agent or improving the anode production process. The scheme for improving the anode production process is different from the technical idea of ​​the present invention, so it is not repeated here. In the prior art scheme for improving the impregnating agent, for example, patent document 202111260444.5 previously applied for by the inventor's team discloses a carbon material impregnating agent and its preparation and application process. The impregnating agent is a colloid formed by blending 1-60wt% of carbon material, a total amount of no more than 10wt% of a treating agent and water in a certain proportion, and is characterized in that, by mass fraction, it is composed of the following components: carbon black 20wt%-40wt%; graphite 1wt%-20wt%; oxidant 0.01wt%-5wt%; coupling agent 0.01wt%-5wt%; dispersant 0.01wt%-5wt%; thickener 0.01wt%-5wt%. For example, patent document 202111260445.X discloses a flexible graphite impregnating agent formula and its preparation and application process. The impregnating agent is composed of the following components by mass fraction: 1-40wt% flexible graphite; the treating agent is not more than 10wt%, and the remaining component is water; wherein the treating agent is composed of an oxidant, a coupling agent, a dispersant, and a thickener. For example, patent document 202111260354.6 discloses a silicon-boron system impregnating agent, which is a solution prepared by blending 0.001%-10% silicon series, 0.001%-10% boron series, no more than 10% auxiliary agent, and 80%-99% water in a certain proportion. Although the above-mentioned impregnating agent can directly or indirectly reduce the ineffective oxidation in the anode pores to a certain extent, the improvement of the air permeability index of the product is relatively limited; for example, patent document 201910052706.5 discloses a method for preparing an impregnating agent for a densified anode carbon block, comprising the following steps: A) mixing coal tar and a solvent at 80 to 135°C to obtain a coal tar solution; the solvent includes washing oil and kerosene; B) centrifuging the coal tar solution, and distilling the upper liquid under reduced pressure; C) mixing the product after the reduced pressure distillation with nano-carbon powder to obtain an impregnating agent for a densified anode carbon block; the average particle size of the nano-carbon powder is 0.02 to 1.5 μm; the mass ratio of the nano-carbon powder to the coal tar is 2 to 4:10. For example, patent document 201410159735.9 discloses a method for preparing anode material for fluorine production using needle coke. The raw materials are 1-0.5mm oil-based needle coke, 0.5-0mm petroleum coke, 200 mesh petroleum coke, and high-temperature hard asphalt adhesive. The weight ratio is 1-0.5mm oil-based needle coke: 0.5-0mm petroleum coke: 200 mesh petroleum coke: high-temperature hard asphalt adhesive = (20±5): (25±5): (55±5): (35±3), and it is made by one impregnation and two roastings.For example, patent document CN202210978631.5 discloses a method for preparing a prebaked anode for aluminum electrolysis, comprising the following steps: placing a prebaked anode block for aluminum electrolysis in an impregnating agent for impregnation treatment to obtain an impregnated block; the impregnating agent is modified asphalt; the impregnated block is first roasted to obtain a roasted block; the roasted blocks are assembled to obtain a prebaked anode for aluminum electrolysis. The present invention can increase the weight of the prebaked anode for aluminum electrolysis, increase its volume density, and reduce its porosity by impregnating and roasting the prebaked anode block for aluminum electrolysis, thereby facilitating the reduction of its air permeability and improving its conductivity. During use, it has the advantages of low pressure drop, long pole replacement cycle, basically no carbon slag, and high current efficiency. The above-mentioned impregnating agents are composed of coal tar, needle coke, and petroleum coke as the main raw materials to form a special impregnating agent, and then the tissue enters the anode opening gap, and a high energy consumption process of secondary roasting is required to meet the use requirements of the electrolytic cell. The process has high energy consumption and needs to be carried out in a special roasting furnace, which requires high investment and site space, making industrial promotion more difficult. Summary of the invention

[0005] The present invention provides a carbon material modified impregnating agent and a preparation method and application thereof, which can significantly reduce the air permeability of the carbon material by post-intervention of the anode carbon material, improve the anode's anti-permeability and service life, and solve the technical problem of poor technical indicators of the current anode process for electrolytic aluminum.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A carbon material modified impregnating agent comprises the following components in parts by weight: 10-70 parts of component A, 5-30 parts of component B, 0.5-15 parts of component C and a solvent; the component A comprises at least one of aluminum sol and aluminum silicate sol; the component B comprises at least one of boron hydroxide, boric acid and borate; the component C comprises at least one of a silane impregnating agent, an organosilicon resin and a silane coupling agent.

[0007] The design idea of ​​the above technical solution is that the modified impregnating agent of the present invention is mainly effective through the combined use of component A, component B and component C, and the composite synergistic interaction of A and B at room temperature is used to make the primary crystal grow and increase the crystal particle size while making the particle size distribution uniform. A three-dimensional network solidification is formed under the process of room temperature dehydration or low temperature drying dehydration, which increases the basic adhesion of the impregnating agent before dehydration into the tank, so that the impregnating agent can be evenly attached to the pore wall and channel concave points of the carbon material, providing basic conditions and a good environment for subsequent secondary curing; and then it is combined with component C as a reinforcing agent under a high temperature environment, and the reinforcing agent uniformly dispersed and interwoven between the components is used in the subsequent high temperature environment of the carbon material (such as the anode in the electrolytic cell preheating process and due to the anode During the temperature rise of the consumption reduction process, it is secondary cured and strengthened with other components. Along with the dynamic curing process, the impregnating material has a certain flow rate under the thermal action set by the components inside the carbon material cavity, so that the pore wall of the carbon material forms a continuous high-temperature resistant corrugated sagging attachment, and a discontinuous high-temperature resistant sagging blocking closed accumulation point is formed at the concave point of the channel, thereby forming a discontinuous closed barrier point in the continuous volatilization channel of the gas brought by the anode cavity, so as to achieve the effect of reducing the gas permeation of the carbon material. The synergistic effect of the continuous high-temperature resistant corrugated attachment and the discontinuous high-temperature resistant sagging can further reduce the surface reactivity of the internal structure, increase the loss along the gas flow, and comprehensively improve the process technical indicators such as the permeability resistance and service life of the carbon material.

[0008] As a further preferred embodiment of the above technical solution, the carbon material modified impregnant further comprises 0.01 to 5 parts by mass of rare earth oxide, wherein the rare earth oxide comprises at least one of cerium oxide, cerium lanthanum oxide and cerium praseodymium oxide. The rare earth oxide of the lanthanide element in the +3 oxidation state inhibits the further growth of the composite crystal at high temperature, optimizes the uniform microstructure of the material, improves the high temperature mechanical properties and adsorption properties of the material, promotes the overall strengthening of the impregnated solid, improves the microstructure of the impregnated sintered body, and has a doping modification effect, and further plays a high temperature step comprehensive reinforcement role on the composite impregnated body.

[0009] As a further preferred embodiment of the above technical solution, the carbon material modified impregnating agent also includes 0.1 to 8 parts by weight of a comprehensive auxiliary agent; the auxiliary agent is one or more of a dispersing, suspending, adhesion promoter and thickening comprehensive auxiliary agent.

[0010] Based on the same technical concept, the present invention also provides a method for preparing the above-mentioned carbon material modified impregnating agent, comprising the following steps: (1) Grind and dissociate the powder material of component B after crushing it, and then screen and grade it after dissociation; (2) The screened and classified powder material is mixed with component A, component C and a solvent and dispersed evenly to obtain the carbon material modified impregnating agent.

[0011] Based on the same technical concept, the present invention also provides an application of the above-mentioned carbon material modified impregnating agent, which can be used to perform complete impregnation treatment and surface impregnation treatment on the anode used in the aluminum electrolysis process.

[0012] The carbon material modified impregnating agent of the present invention can be used for complete impregnation treatment or surface impregnation treatment of the anode used in the aluminum electrolysis process to reduce the overall or local permeability of the material. When used for complete impregnation treatment of the anode, it can be used alone as an anode complete impregnating agent, or it can be used in combination with other common impregnating agents. When used in combination, it can significantly improve the air permeability of the anode while ensuring that the common impregnating agent improves the air reactivity and carbon dioxide reactivity of the anode; when used for surface impregnation treatment of the anode, it can also be used alone or in combination with a special anode coating. Before the construction of the anode coating, the carbon material modified impregnating agent of the present invention is used to modify the anode surface first, so as to comprehensively improve the use effect of the coating.

[0013] The present invention utilizes a specific carbon material modified impregnating agent to carry out impregnation treatment on the anode of the aluminum electrolysis process device. In addition to the above-mentioned effect of increasing the anti-permeability, the working environment of the anode in the electrolysis process and the high temperature section of the electrolytic cell can also be utilized to enable the impregnating agent to achieve secondary solidification and strengthening, thereby avoiding the high energy consumption and high cost problems caused by the need for secondary calcination of the existing impregnating agent to meet the requirements of the electrolysis process. When used in conjunction with the existing anode post-intervention technology on the market, the use scenarios of the impregnating agent are broadened, the convenience of use is improved, and the cost of use is significantly reduced.

[0014] As a further preferred embodiment of the above technical solution, when the anode used in the aluminum electrolysis process is completely impregnated with the carbon material modified impregnant, the following steps are included: (1) removing large dust particles from the surface of the anode; (2) placing the anode into an immersion tank for immersion, and taking it out after immersion for drying and curing; (3) Assemble the dried and cured anode into the tank for use.

[0015] As a further preferred embodiment of the above technical solution, when the carbon material modified impregnating agent is used to perform surface impregnation treatment on the anode used in the aluminum electrolysis process, the following steps are included: (1) removing large dust particles from the surface of the anode; (2) applying the carbon material modified impregnating agent on the surface of the anode, taking it out after impregnation and drying and curing it; (3) Assemble the dried and cured anode into the tank for use.

[0016] As a further preferred embodiment of the above technical solution, after drying and curing in step (2), the water content of the impregnant on the surface of the anode is ≤15%.

[0017] As a further preferred embodiment of the above technical solution, when the anode used in the aluminum electrolysis process is completely impregnated with the carbon material modified impregnating agent, the carbon material modified impregnating agent can be compounded with other common impregnating agents for use.

[0018] As a further preferred embodiment of the above technical solution, when the anode used in the aluminum electrolysis process is subjected to surface impregnation treatment with the carbon material modified impregnating agent, other coatings may be used to coat the surface of the anode after drying and curing in step (2).

[0019] As a further preferred embodiment of the above technical solution, when the anode used in the aluminum electrolysis process is surface impregnated with the carbon material modified impregnating agent, the drying and curing time of step (2) is more than 24 hours.

[0020] As a further preferred embodiment of the above technical solution, when the anode used in the aluminum electrolysis process is surface impregnated with the carbon material modified impregnant and the surface of the anode is coated with other coatings after drying and curing in step (2), the drying and curing time of step (2) is more than 8 hours, and the curing time of the coating after coating is more than 12 hours.

[0021] Compared with the prior art, the advantages of the present invention are: The carbon material modified impregnating agent of the present invention can significantly reduce the air permeability of the carbon material, improve the material's anti-permeability and service life, thereby improving the process technical indicators of the carbon material. The main raw materials are all organic components and have good compatibility and dispersibility with aqueous solutions. It has the advantages of being environmentally friendly, non-toxic and harmless, and easy to prepare, and meets the requirements of green production. When applied to the treatment of anodes used in aluminum electrolysis processes, it can significantly reduce the use cost and improve the convenience of use. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with specific embodiments.

[0023] Example 1: (whether to keep single variables 1-3, whether to add examples to adjust the group allocation ratio) The carbon material modified impregnating agent of this embodiment includes the following components in parts by weight: 10 parts of component A, 5 parts of component B, 0.5 parts of component C, 0.2 parts of dispersant, 0.1 parts of suspending agent, 0.1 parts of adhesion promoter, 0.1 parts of thickener and 84 parts of solvent water; wherein component A is aluminum sol; component B is boron hydroxide; component C is a silane coupling agent.

[0024] The preparation method of the carbon material modified impregnating agent of this embodiment comprises the following steps: (1) Component B is crushed by a crusher, and the crushed powder is screened using a 1250 mesh screen. The powder that cannot pass through the screen is returned to the crusher for re-crushing until the particle size requirements are met; (2) The powder material obtained after the crushing is ground and dissociated, and then classified, screened and modified after dissociation, and then mixed with component A, component C, dispersant and solvent and stirred evenly at a stirring speed of 350 r / min to obtain the carbon material modified impregnating agent of this embodiment.

[0025] The carbon material modified impregnating agent of this embodiment is used to completely impregnate the anode material used in the aluminum electrolysis process. The specific method includes the following steps: (1) Blow the surface of the anode material to remove large particles of dust on its surface, so that its surface dustiness is ≤ Level 3 (reference standard: GB / T18570.3); (2) The anode material of step (1) is placed in the carbon material modified impregnating agent of this embodiment for complete impregnation, and after impregnation, it is left to dry and solidify at a drying temperature of 50° C. and a drying time of 36 h. After drying and solidification, the water content of the impregnating agent on the surface of the anode material is 10%; (3) Assemble the dried and solidified anode material into the cell for use.

[0026] The anode material impregnated with the carbon material modified impregnant of this embodiment is tested, and the test method is as follows: With reference to standards YS / T63.23-2012 "Test methods for carbon materials for aluminum Part 23: Determination of air reactivity of prebaked anodes by thermogravimetric method", YS / T63.24-2012 "Test methods for carbon materials for aluminum Part 24: Determination of carbon dioxide reactivity of prebaked anodes by thermogravimetric method" and YS / T63.10-2012 "Test methods for carbon materials for aluminum Part 10: Determination of air permeability", the air reactivity, carbon dioxide reactivity and air permeability of ordinary anode materials and modified impregnation-treated anode materials were tested respectively. The test results are shown in Table 1.

[0027] Embodiment 2: The carbon material modified impregnating agent of this embodiment includes the following components in parts by weight: 12.5 parts of component A, 6 parts of component B, 0.5 parts of component C, 0.4 parts of dispersant, 0.2 parts of suspending agent, 0.2 parts of adhesion promoter, 0.15 parts of thickener, 0.05 parts of rare earth oxide (cerium oxide) and 80 parts of solvent water; wherein component A is aluminum sol; component B is boron hydroxide; component C is silane impregnating agent.

[0028] The preparation method of the carbon material modified impregnating agent of this embodiment comprises the following steps: The carbon material modified impregnating agent of this embodiment is used to completely impregnate the anode material used in the aluminum electrolysis process. The specific method includes the following steps: (1) Blow the surface of the anode material to remove large particles of dust on its surface, so that its surface dustiness is ≤ Level 3 (reference standard: GB / T18570.3); (2) The anode material of step (1) is placed in the carbon material modified impregnating agent of this embodiment for complete impregnation, and after impregnation, it is left to dry and solidify at a temperature of 60° C. for 30 hours. After drying and solidification, the water content of the impregnating agent on the surface of the anode material is 9%; (3) Assemble the dried and solidified anode material into the cell for use.

[0029] The anode material impregnated with the carbon material modified impregnant of this embodiment is tested, and the test method is as follows: With reference to standards YS / T63.23-2012 "Test methods for carbon materials for aluminum Part 23: Determination of air reactivity of prebaked anodes by thermogravimetric method", YS / T63.24-2012 "Test methods for carbon materials for aluminum Part 24: Determination of carbon dioxide reactivity of prebaked anodes by thermogravimetric method" and YS / T63.10-2012 "Test methods for carbon materials for aluminum Part 10: Determination of air permeability", the air reactivity, carbon dioxide reactivity and air permeability of ordinary anode materials and modified impregnation-treated anode materials were tested respectively. The test results are shown in Table 1.

[0030] Embodiment 3: The carbon material modified impregnating agent of this embodiment includes the following components in parts by weight: 10 parts of component A, 6 parts of component B, 0.5 parts of component C, 0.2 parts of dispersant, 0.15 parts of suspending agent, 0.1 parts of adhesion promoter, 0.1 parts of thickener, 0.05 parts of rare earth oxide (cerium oxide) and 83 parts of solvent water; wherein component A is aluminum sol and aluminum silica sol (mass ratio is 1:1); component B is boron hydroxide and boric acid (mass ratio is 2:1); component C is silicone resin.

[0031] The preparation method of the carbon material modified impregnating agent of this embodiment comprises the following steps: (1) Component B is crushed by a crusher, and the crushed powder is screened using a 1250 mesh screen. The powder that cannot pass through the screen is returned to the crusher for re-crushing until the particle size requirements are met; (2) The powder material obtained after the crushing is ground and dissociated, and then classified, screened and modified after dissociation, and then mixed with component A, component C, suspending agent, adhesion promoter, thickener, dispersant, rare earth oxide and solvent and stirred evenly at a stirring speed of 200 r / min to obtain the carbon material modified impregnating agent of this embodiment.

[0032] The carbon material modified impregnating agent of this embodiment is used to completely impregnate the anode material used in the aluminum electrolysis process. The specific method includes the following steps: (1) Blow the surface of the anode material to remove large particles of dust on its surface, so that its surface dustiness is ≤ Level 3 (reference standard: GB / T18570.3); (2) The anode material of step (1) is placed in the carbon material modified impregnating agent of this embodiment for complete and separate impregnation. After impregnation, it is allowed to stand and air-dry and solidify for 48 hours. After air-drying and solidification, the moisture content of the impregnating agent on the surface of the anode material is 14%; (3) Assemble the air-dried and solidified anode material into the tank for use.

[0033] The anode material impregnated with the carbon material modified impregnant of this embodiment is tested, and the test method is as follows: With reference to standards YS / T63.23-2012 "Test methods for carbon materials for aluminum Part 23: Determination of air reactivity of prebaked anodes by thermogravimetric method", YS / T63.24-2012 "Test methods for carbon materials for aluminum Part 24: Determination of carbon dioxide reactivity of prebaked anodes by thermogravimetric method" and YS / T63.10-2012 "Test methods for carbon materials for aluminum Part 10: Determination of air permeability", the air reactivity, carbon dioxide reactivity and air permeability of ordinary anode materials and modified impregnation-treated anode materials were tested respectively. The test results are shown in Table 1.

[0034] Embodiment 4: The carbon material modified impregnating agent of this embodiment includes the following components in parts by weight: 20 parts of component A, 8 parts of component B, 1 part of component C, 0.5 parts of dispersant, 0.1 parts of suspending agent, 0.1 parts of adhesion promoter, 0.2 parts of thickener, 0.1 parts of rare earth oxide (cerium oxide and cerium lanthanum oxide, mass ratio is 1:1) and 70 parts of solvent water; wherein component A is aluminum sol and aluminum silica sol (mass ratio is 3:1); component B is boron hydroxide and boric acid (mass ratio is 1:1); component C is silicone resin.

[0035] The preparation method of the carbon material modified impregnating agent of this embodiment comprises the following steps: (1) Component B is crushed by a crusher, and the crushed powder is screened using a 1250 mesh screen. The powder that cannot pass through the screen is returned to the crusher for re-crushing until the particle size requirements are met; (2) The powder material obtained after the crushing is ground and dissociated, and then classified, screened and modified after dissociation, and then mixed with component A, component C, suspending agent, adhesion promoter, thickener, dispersant, rare earth oxide and solvent and stirred evenly at a stirring speed of 200 r / min to obtain the carbon material modified impregnating agent of this embodiment.

[0036] The carbon material modified impregnating agent of this embodiment is used to perform surface impregnation treatment on the anode material used in the aluminum electrolysis process. The specific method includes the following steps: (1) Blow the surface of the anode material to remove large particles of dust on its surface, so that its surface dustiness is ≤ Level 3 (reference standard: GB / T18570.3); (2) The anode material in step (1) is coated with the carbon material modified impregnating agent of this embodiment for surface impregnation, and then allowed to stand for air drying and curing. After air drying and curing for 48 hours, the water content of the impregnating agent on the surface of the anode material is 12%; (3) Assemble the air-dried and solidified anode material into the tank for use.

[0037] The anode material impregnated with the carbon material modified impregnant of this embodiment is tested, and the test method is as follows: With reference to standards YS / T63.23-2012 "Test methods for carbon materials for aluminum Part 23: Determination of air reactivity of prebaked anodes by thermogravimetric method", YS / T63.24-2012 "Test methods for carbon materials for aluminum Part 24: Determination of carbon dioxide reactivity of prebaked anodes by thermogravimetric method" and YS / T63.10-2012 "Test methods for carbon materials for aluminum Part 10: Determination of air permeability", the air reactivity, carbon dioxide reactivity and air permeability of ordinary anode materials and modified impregnation-treated anode materials were tested respectively. The test results are shown in Table 1.

[0038] The anode material treated by the impregnation of the carbon material modified impregnant of this embodiment is used in the aluminum electrolysis process, and the anode material heated in the high temperature section of the electrolytic cell is tested. The test method is as follows: The air permeability and sealing amount of the combined coating were tested with reference to the standard YS / T63.10-2012 "Test methods for carbon materials for aluminum Part 10: Determination of air permeability" and "A test method for sealing performance of prebaked anode coating materials". The test results are shown in Table 2.

[0039] The calculation of the sealing amount is based on the loss on ignition; the loss on ignition is the percentage of the mass lost after burning at a high temperature of 600℃-1000℃ for a long enough time (≥24h) to the mass of the original sample; Standardize the test method of closed quantity to form internal control documents; "A method for testing the sealing performance of preliminary anode coating materials" will be jointly declared with the present invention.

[0040] Table 1. Performance test results of various embodiments

[0041] Table 2. Closure loss rate test results of Example 4

[0042] Comparative Example 1: The carbon material impregnating agent of this comparative example comprises the following components in the following proportions: 10 parts of component A, 5 parts of component B, 0.5 parts of dispersant, 0.1 parts of suspending agent, 0.2 parts of adhesion promoter, 0.2 parts of thickener and 85 parts of solvent water; wherein component A is aluminum sol; component B is boron hydroxide.

[0043] The preparation method of the carbon material modified impregnating agent in this comparative example is the same as that in Example 1.

[0044] The anode material impregnated with the carbon material modified impregnant of this comparative example was tested in the same manner as in Example 1. The test results are shown in Table 3.

[0045] Comparative Example 2: The carbon material impregnating agent of this comparative example comprises the following components in the following proportions: 8 parts of component A, 4 parts of component B, 0.3 parts of component C, 0.1 parts of dispersant, 0.2 parts of suspending agent, 0.2 parts of adhesion promoter, 0.2 parts of thickener and 87 parts of solvent water; wherein component A is aluminum sol; component B is boron hydroxide; component C is silane impregnating agent.

[0046] The preparation method of the carbon material modified impregnating agent in this comparative example is the same as that in Example 1.

[0047] The anode material impregnated with the carbon material modified impregnant of this comparative example was tested in the same manner as in Example 1. The test results are shown in Table 3.

[0048] Table 3 Comparison of air permeability and sealing loss rate

[0049] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A carbon material modified impregnating agent, characterized in that: The composition comprises the following components in parts by weight: 10-70 parts of component A, 5-30 parts of component B, 0.5-15 parts of component C and a solvent; the component A comprises at least one of aluminum sol and aluminum silicate sol; the component B comprises at least one of boron hydroxide, boric acid and borate; the component C comprises at least one of a silane impregnating agent, an organosilicon resin and a silane coupling agent.

2. The carbon material modified impregnating agent according to claim 1, characterized in that: The invention also includes 0.01 to 5 parts by mass of a rare earth oxide, wherein the rare earth oxide includes at least one of cerium oxide, cerium lanthanum oxide and cerium praseodymium oxide.

3. The carbon material modified impregnating agent according to claim 1 or 2, characterized in that: The invention also includes 0.1 to 8 parts by weight of an auxiliary agent; the auxiliary agent includes at least one of a dispersant, a suspending agent, an adhesion promoter and a thickener.

4. A method for preparing a carbon material modified impregnating agent according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) The powder material of component B is crushed, ground and dissociated, and then screened and classified; (2) The screened and classified powder material is mixed with component A, component C and a solvent and dispersed evenly to obtain the carbon material modified impregnating agent.

5. The method for preparing a carbon material modified impregnating agent according to claim 4, characterized in that: The stirring rate during the mixing process in step (2) is set to 100-500 r / min.

6. Use of a carbon material modified impregnating agent according to any one of claims 1 to 3 or a carbon material modified impregnating agent obtained by the preparation method according to any one of claims 4 to 5, characterized in that: The carbon material modified impregnating agent is used for impregnating the anode used in the aluminum electrolysis process.

7. The use of the carbon material modified impregnating agent according to claim 6, characterized in that: The carbon material modified impregnating agent is used for performing complete impregnation treatment or surface impregnation treatment on the anode used in the aluminum electrolysis process.

8. The use of the carbon material modified impregnating agent according to claim 7, characterized in that: The complete impregnation of anodes used in the aluminum electrolysis process includes the following steps: (1) removing large dust particles from the surface of the anode; (2) placing the anode into an impregnation tank containing the carbon material modified impregnant for impregnation, and taking it out after impregnation for drying and curing; (3) Assemble the dried and cured anode into the tank for use.

9. The use of the carbon material modified impregnating agent according to claim 7, characterized in that: The surface impregnation treatment of the anode used in the aluminum electrolysis process includes the following steps: (1) removing large dust particles from the surface of the anode; (2) applying the carbon material modified impregnating agent on the surface of the anode, taking it out after impregnation and drying and curing it; (3) Assemble the dried and cured anode into the tank for use.

10. The use of the carbon material modified impregnating agent according to claim 8 or 9, characterized in that: After drying and curing in step (2), the water content of the impregnant on the surface of the anode is ≤15%.

Citation Information

Patent Citations

  • Method for preparing anode material for preparing fluorine by utilizing needle coke

    CN104372373A

  • An impregnating agent for encrypted anode carbon blocks and its preparation method

    CN109518230B

  • Flexible graphite impregnant formula and preparation and application process thereof

    CN113912421A

  • A high-efficiency silicon-boron system impregnating agent formula and its preparation and application process

    CN114016087B

  • A carbon material impregnating agent and its preparation and application process

    CN114031421B